1998
DOI: 10.2337/diacare.21.11.1836
|View full text |Cite
|
Sign up to set email alerts
|

Association of waist circumference with risk of hypertension and type 2 diabetes in Nigerians, Jamaicans, and African-Americans.

Abstract: O B J E C T I V E -Prior studies have supported that waist circ u m f e rence correlates better with visceral adipose tissue and is a better predictor of cardiovascular disease than are BMI and waist-to-hip ratio. In this study, we reexamine the role of waist size on the risk of hypert e n s i o n and type 2 diabetes in African-origin populations from three contrasting enviro n m e n t s . RESEARCH DESIGN AND METHODS-A cross-sectional survey was conducted of 5,042 men and women 25-74 years of age from Nigeria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
74
1
5

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 3 publications
4
74
1
5
Order By: Relevance
“…9 Previous studies have consistently shown that obesity is associated with increased risks of diabetes. [10][11][12][13][14][15][16][17][18][19] The WHO defines obesity as a condition with excessive fat accumulation in the body to the extent that health and well-being are adversely affected. 20 Although there are many methods available to measure absolute total fat and adipose tissue distribution other than anthropometric measurements, their associated high cost prevents their use in large-scale epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 Previous studies have consistently shown that obesity is associated with increased risks of diabetes. [10][11][12][13][14][15][16][17][18][19] The WHO defines obesity as a condition with excessive fat accumulation in the body to the extent that health and well-being are adversely affected. 20 Although there are many methods available to measure absolute total fat and adipose tissue distribution other than anthropometric measurements, their associated high cost prevents their use in large-scale epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…22 Waist-hip ratio (WHR) and waist circumference (WC) measure central fat deposition. 10,11 These anthropometric measurements have been shown to be associated with diabetes and cardiovascular diseases. [10][11][12][13][14][15][16][17][18][19] Available data on the relation-ships between obesity and adverse health outcomes are mostly from Europe and the United States.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a large body of epidemiologic evidence links abdominal obesity with increased risk of many cardiovascular diseases (CVD), [1][2][3][4][5][6][7][8] the mechanism for the association is not clear. Elevated total cholesterol and lipoproteins through atherogenic and thrombotic processes have been hypothesised in the association of abdominal adiposity with CVD.…”
Section: Introductionmentioning
confidence: 99%